Inhibition of Breast Cancer Cell Migration by Cyclotides Isolated from Pombalia calceolaria - Pinto, Meri Emili F. [UNESP]; Najas, Jhenny Z. G.; Magalhães, Luma G.; Bobey, Antonio F. [UNESP]; Mendonça, Jacqueline N.; Lopes, Norberto P.; Leme, Flávia M.; Teixeira, Simone P.; Trovó, Marcelo; Andricopulo, Adriano D.; Koehbach, Johannes; Gruber, Christian W.; et al. (American Chemical Society (ACS), 2018)
Two new bracelet cyclotides from roots of Pombalia calceolaria with potential anticancer activity have been characterized in this work. The cyclotides Poca A and B (1 and 2) and the previously known CyO4 (3) were de novo sequenced by MALDI-TOF/TOF mass spectrometry (MS). The MS2 spectra were examined and the amino acid sequences were determined. The purified peptides were tested for their cytotoxicity and effects on cell migration of MDA-MB-231, a triple-negative breast cancer cell line. The isolated cyclotides reduced the number of cancer cells by more than 80% at 20 μM, and the concentration-related cytotoxic responses were observed with IC50 values of 1.8, 2.7, and 9.8 μM for Poca A (1), Poca B (2), and CyO4 (3), respectively. Additionally, the inhibition of cell migration (wound-healing assay) exhibited that CyO4 (3) presents an interesting activity profile, in being able to inhibit cell migration (50%) at a subtoxic concentration (2 μM). The distribution of these cyclotides in the roots was analyzed by MALDI imaging, demonstrating that all three compounds are present in the phloem and cortical parenchyma regions.